Let’s learn how to do 1 term × 1 term multiplication

Like

#### 2x × 3y

= 2 × 3 × x × y

= 6xy

####
4x
^{
3
}
× 3x
^{
2
}
y

= 4 × 3 × x
^{
3
}
× x
^{
2
}
× y

= 12 × x
^{
3 + 2
}
× y

= 12x
^{
5
}
y

#### x × 3y

= 3 × x × y

= 3xy

####
5x × (–3y
^{
2
}
x
^{
3
}
)

= 5 × (−3) × x × x
^{
3
}
× y
^{
2
}

= −15 × x
^{
1 + 3
}
× y
^{
2
}

= −15x
^{
4
}
y
^{
2
}

####
4xy × 5x
^{
2
}
y
^{
2
}
× 6x
^{
3
}
y
^{
3
}

= 4 × 5 × 6 × x × x
^{
2
}
× x
^{
3
}
× y × y
^{
2
}
× y
^{
3
}

= 20 × 6 × x
^{
1 + 2 + 3
}
× y
^{
1 + 2 + 3
}

= 120x
^{
6
}
y
^{
6
}